Insects’ RNA Profiling Reveals Absence of “Hidden Break” in 28S Ribosomal RNA Molecule of Onion Thrips, Thrips tabaci - Rosaline Wanjiru Macharia; Fidelis Levi Ombura; Erick Onyango Aroko (Journal of Nucleic Acids)
With an exception of aphids, insects’ 28S rRNA is thought to harbor a “hidden break” which cleaves under denaturing conditions to comigrate with 18S rRNA band to exhibit a degraded appearance on native agarose gels. The degraded appearance confounds determination of RNA integrity in laboratories that rely on gel electrophoresis. To provide guidelines for RNA profiles, RNA from five major insect orders, namely, Diptera, Hemiptera, Thysanoptera, Hymenoptera, and Lepidoptera, was compared under denaturing and nondenaturing conditions. This study confirmed that although present in most of insect’s RNA, the “hidden break” is absent in the 28S rRNA of onion thrips, Thrips tabaci. On the other hand, presence of “hidden break” was depicted in whiteflies’ 28S rRNA despite their evolutionary grouping under same order with aphids. Divergence of 28S rRNA sequences confirms variation of both size and composition of gap region among insect species. However, phylogeny reconstruction does not support speciation as a possible source of the hidden break in insect’s 28S rRNA. In conclusion, we show that RNA from a given insect order does not conform to a particular banding profile and therefore this approach cannot be reliably used to characterize newly discovered species.